Beneficial Microorganisms in Agriculture, Food and the Environment: Safety Assessment and Regulation - Sundh, Ingvar (CABI, 2014)
Microorganisms have been vital in the evolution of life on earth and they play paramount roles in the environment as well as for humankind. The earliest examples of active human exploita- tion of their activities are microbes that were ‘domesticated’ thousands of years ago for use in bread, alcohol fermentations and dairy products. Alongside societal development and strong growth in our understanding of the nature and properties of microorganisms, and the ability to culture single microbial isolates, several additional fields of application have surfaced within the agricultural, environmental and biotechnological sectors. However, with the realization during the last two centuries that many serious diseases are due to microorganisms causing infections or producing toxic compounds, it has become obvious that large-scale culture, mar- keting and utilization of single isolates of living microorganisms necessitate a careful safety assessment. Thus, a microorganism cannot be considered truly ‘beneficial’ until a certain level of safety has been established. As a consequence, many types of applications with microorgan- isms are presently subject to various regulatory measures. The introduction of regulatory systems can have consequences for the inclination of research entrepreneurs and industry to venture into new projects with beneficial microorgan- isms. Long and costly registration procedures that are not commensurate with actual risks can unnecessarily hamper the development of useful microbiological products. Conversely, lack of appropriate regulation could potentially result in serious negative consequences for public health or for the environment. Many different types of legislation are applicable to the market- ing and use of microbiological products. General acts of legislation – e.g. regarding consumer, occupational or environmental safety – cover the marketing and use of beneficial microorgan- isms, and state that the producer or manufacturer of a product is responsible for an adequate safety assessment. In other specific cases, the submission of a data dossier followed by authori- zation is a prerequisite for market introduction.